A "clean cigarette" for a clean nation: a case study of Salem Pianissimo in Japan. (24th November 2004) - Assunta, M; Chapman, S
Abstract : Objective: To illustrate, through internal industry documents, how RJ Reynolds exploited the concerns of the Japanese society about cleanliness to market the concept of cleaner, implicitly healthier cigarettes in Japan. Design: Systematic keyword and opportunistic website searches of formerly private internal industry documents. Results: Industry documents show that RJ Reynolds developed marketing plans based upon their cultural assumptions of Japanese people as fastidious about hygiene and manners, and with relatively high penchants to try new products. RJ Reynolds found there was also a growing concern for health, the environment, and smokers were conscious about annoying others. Deodorised consumer products were one of Japan's biggest trends. These characteristics presented RJ Reynolds with a profitable formula for marketing Salem Pianissimo, a clean cigarette with less smell and smoke. Salem Pianissimo, a 100 mm cigarette claiming to contain 1 mg tar and 0.1 mg nicotine, targeted women since menthol cigarettes were popular among 18–24 year old female smokers, although Japan's law prohibited those below 20 years to smoke and the tobacco industry had a voluntary code disallowing advertising to women and youth. Conclusion: RJ Reynolds successfully launched its clean cigarette, Salem Pianissimo, in Japan aiming to exploit perceived cultural characteristics such as a penchant for cleanliness, an eagerness to try new products, and social harmony.